2017
DOI: 10.1515/ijamh-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

Tubo-ovarian abscess in non sexually active adolescents

Abstract: A tubo-ovarian abscess is a rare presentation in non-sexually active adolescents; only 11 cases have been reported in the literature. Variable approaches for diagnosis and management are described. We present a 19-year-old, non-sexually active, medically free girl, who had an abdominopelvic mass with abdominal pain and vomiting followed by fever. She had a confusing presentation of malignancy versus tuberculosis, with the help of imaging, diagnosis and treatment with percutaneous drainage, conservative treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…Approximately, three quarters of patients had anatomic abnormalities and/or other disease processes that increased their risk of TOA, such as renal agenesis, appendicitis, and renal or urinary tract anomalies. The authors concluded that TOAs are not limited to sexually active females.Prior case reports of TOA in nonsexually active women are consistent with the findings of Hakim et al Two literature reviews summarize 11 cases of TOAs in nonsexually active adolescents [5,6]. Isolated organisms included Escherichia coli, Bacteroides fragilis, Bacteroides species, Peptostreptococcus, Peptococcus, and aerobic Streptococcus.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Approximately, three quarters of patients had anatomic abnormalities and/or other disease processes that increased their risk of TOA, such as renal agenesis, appendicitis, and renal or urinary tract anomalies. The authors concluded that TOAs are not limited to sexually active females.Prior case reports of TOA in nonsexually active women are consistent with the findings of Hakim et al Two literature reviews summarize 11 cases of TOAs in nonsexually active adolescents [5,6]. Isolated organisms included Escherichia coli, Bacteroides fragilis, Bacteroides species, Peptostreptococcus, Peptococcus, and aerobic Streptococcus.…”
supporting
confidence: 71%
“…Prior case reports of TOA in nonsexually active women are consistent with the findings of Hakim et al Two literature reviews summarize 11 cases of TOAs in nonsexually active adolescents [5,6]. Isolated organisms included Escherichia coli, Bacteroides fragilis, Bacteroides species, Peptostreptococcus, Peptococcus, and aerobic Streptococcus.…”
supporting
confidence: 71%